Analisis Pola Konsumsi Menurut Perspektif Ekonomi Islam (Studi Kasus pada Penghuni Kos Putri Ponorogo) - Putri Maghfi (Lisyabab : Jurnal Studi Islam dan Sosial, 2021)
The activity of using goods or services to meet the needs of one's life is also known as consumption. Consumption activities, especially for a Muslim, are not only to meet needs and satisfaction but also to achieve the benefits of the world and the hereafter. However, with the changing times like today, namely the modern era where many people buy goods and services not only because of the benefits or needs but also influenced by lifestyle so that they cannot distinguish which are really basic needs and which are just desires. to make it more trendy or up to date by others. This is very inversely proportional to the practice with the existing theory in the consumption of Islamic Economics. The purpose of writing this article is to find out the consumption pattern of the community and what factors influence the consumption pattern of the community itself. This research includes descriptive qualitative research and includes field research using data in the form of observations and interviews. The results of this study indicate that people's consumption patterns do not match the existing practice with existing theories, causing excessive consumption. Excessive consumption can lead to tabzir (wrong use of wealth so that it violates sharia rules) and israf (excessive use of property in several cases). The factors that cause a person's consumption behavior are external factors which are divided into two, namely cultural or social and reference groups. This socio-cultural factor is related to the habits, lifestyle, and the surrounding environment of a person so that it affects his consumptive behavior and the purpose of the reference group is the person's playmates or college friends.